Punk rock and German crisis : adaptation and resistance after 1977 - Shahan, Cyrus (Studies in European culture and history, 2013)
The year 1977 is usually associated with West German terrorism, but it witnessed another cultural watershed: punk music."Punk Rock and German Crisis" asserts, through the lived instance of punk and punk's investment in cultural representation - art, literature, and music - the importance of this sub-cultural moment for understanding the field of contested politics in West Germany. A new reckoning with the legacy of political and aesthetic spaces, this book argues the centrality of punk music for understanding crises of state and terrorist violence, American racism and German fascism, and aesthetic production.